Generalized weighted Morrey spaces and higher order commutators of sublinear operators - Guliyev, V.S. (Eurasian Mathematical Journal, 2012)
In this paper, we study the boundedness of sublinear operators and theirhigher order commutators generated by Calderon-Zygmund operators and Riesz potentials on generalized weighted Morrey space.